A new record family Neopseustidae (Insecta: Lepidoptera) from Chongqing of China, with the first description of the Neopseustis archiphenax female adult - Lv, Jun-Xian; Wang, Xing; Huang, Guo-Hua (Zootaxa, 2023)
In 2022, the insect inventories organized by Prof. Zhi-Sheng Zhang of Southwest University were constructed in Yintiaoling Nature Reserve, Chongqing Municipality, China. The neopseustid moth from Chongqing based on three specimens of Neopseustis archiphenax by light trapping were reported in this paper. The photos of the male and female adults, genitalia, and abdominal special structures are presented with the female described firstly. Also, the DNA barcoding sequence data is provided, and the key to the Neopseustis species is given.